Methodology: training requirement of agriculture extension officers in Iraq - Saleh, Jasim Mohammed; Man, Norsida; Al-Hamdany, Majeed Hadi Saleh (IDOSI Publications, 2016)
Identifying training needs of structural and component in the training industry is an important process that needs to be given a high consideration. It seems difficult to identify training requirements, because of differences in the levels of the trainer experience, skills and efficiency. In-service training of the Extension Agents is the call of the time. Training needs were assessed using the Borich Needs Assessment Model, This Model is designed around the skills individuals and groups need to be effective in the future and are used for making human resources decisions. Will be modified this model with suitable in my country to achieve goal my study. Also I design conceptual framework to explain the dependent and independent variables of the study. The data collection after completed my questionnaire, validity and reliability of the instrument and doing T-test, when collect a data, the data analysis to get result and discussion. Training should not be conducted at the time of sowing and harvesting time and lectures should be carried out during the training sessions and choose time suitable for agricultural extension workers. Thus, necessary steps should be taken to identify the unfelt needs of the agricultural extension workers and strengthen their knowledge, skills and attitudes required for performing their job efficiently.